The simondonian conceptualization of information: an input for the analysis of the digitization of social life - Chibey Rivas, Tamara (Resonancias. Revista de Filosofía, 2021)
This article studies the current phenomenon of digitization and its impact on the social sphere. The question of the article is: In what way can the conceptualization of information according to Gilbert Simondon be a contribution to explain the digitization of social life? As a hypothesis is affirmed that simondonian conceptualization can contribute to the study of the digitalization of social life, because from this, it is possible to, (i) incorporate information technologies and its relation to order; (ii) form a digital culture focused on reception and amplification operations that take place in digital media and (iii) study its paradigmatic nature on the field of digitization, allowing to bet on an adequate broad and transversal conceptualization to the contemporary technological scene, but in itself insufficient.